The Spirit of Implementation of Islamic Sharia in Aceh on the Protection of Women (Case Study in West Aceh District, Bireun and Lhoksemawe City) - Husaini Husda; Bustami Abubakar; Nuraini A. Manan; Nurrahmi Nurrahmi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper aims to reconstruct the image of a just society towards the application of Islamic law in Aceh in various existing regulations, both qanuns, regulations, instructions and appeals. So far, mage has been built through unbalanced research, especially those carried out by supporters of gender equality and human rights in their various studies which always state that women are restrained, marginalized and not given sufficient space in the domestic and public spheres. The research that has been exposed so far has only seen the views of feminists, gender and human rights observers, while academics, ulama, policy makers (executive-legislative) and women "victims" have not been touched by these studies. This is where the importance of this research is to see how the views and opinions of academics, scholars, policy makers (executive-legislative) and women "victims" of the Regulations for the Implementation of Islamic Shari'a in 3 districts/cities in Aceh, namely Aceh Barat, Bireun and City of Lhokseumawe, are important which has issued regulations, instructions and appeals that seem to have a specific object towards women. This field research research uses a qualitative descriptive approach, with data collected through observation, interviews and document review which are then refined by data analysis. This study found that academics, ulama, policy makers (executive-legislative) and women "victims" have different views on the image of Islamic Shari'a in Aceh which has been built from the perspective of supporting gender equality and human rights. It is as if these regulations are acts of discrimination against women, even though they are concrete efforts to protect women. However, there are still many applications in the field, both regarding enforcement procedures and socialization that need to be considered. For this reason, continuous and comprehensive socialization by involving bureaucrats, academics, scholars, community leaders and women through formal and non-formal education channels, Friday pulpits, study groups in ta'lim assemblies, family education and official government channels, such as raids and other preventive measures.